2001
DOI: 10.1152/ajprenal.2001.281.2.f206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary K intake on apical small-conductance K channel in CCD: role of protein tyrosine kinase

Abstract: We have used Western blot to examine the expression of cSrc protein tyrosine kinase (PTK) and protein tyrosine phosphatase (PTP)-1D in the renal cortex, and the patch-clamp technique to determine the role of PTK in mediating the effect of dietary K intake on the small-conductance K (SK) channel in the cortical collecting duct (CCD). When rats were on a K-deficient (KD) diet for 1, 3, 5, and 7 days, the expression of cSrc increased by 40, 90, 140, and 135%, respectively. In contrast, the expression of cSrc in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
101
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(111 citation statements)
references
References 22 publications
7
101
1
Order By: Relevance
“…Sprague-Dawley rats were fed matched diets that were either deficient in K (low-K diet) or high in K content (high-K diet) for 2 days and compared with control (control-K diet). These diets are well established to change Kir1.1 channel density and provoke strong K conservation (low-K diet) or strikingly increased renal K excretion (high-K diet) compared with animals on a control-K diet (22)(23)(24)(25). Quantitative analysis of mRNA levels from the kidneys of these animals using isoform-specific Kir1.1 protein abundance in the presence and absence of WNK1 isoforms.…”
Section: Dominant-negative Regulation Of L-wnk1 By Ks-wnk1mentioning
confidence: 99%
“…Sprague-Dawley rats were fed matched diets that were either deficient in K (low-K diet) or high in K content (high-K diet) for 2 days and compared with control (control-K diet). These diets are well established to change Kir1.1 channel density and provoke strong K conservation (low-K diet) or strikingly increased renal K excretion (high-K diet) compared with animals on a control-K diet (22)(23)(24)(25). Quantitative analysis of mRNA levels from the kidneys of these animals using isoform-specific Kir1.1 protein abundance in the presence and absence of WNK1 isoforms.…”
Section: Dominant-negative Regulation Of L-wnk1 By Ks-wnk1mentioning
confidence: 99%
“…The inhibitory effect of low K intake on renal K secretion is partially achieved by removing renal outer medullary potassium (ROMK)-like small conductance K channels from the apical membrane of principal cells in the cortical collecting duct (CCD) through a protein-tyrosine kinase (PTK)-dependent mechanism (3). We have demonstrated previously that low K intake stimulates the production of superoxide anions and its related products, which in turn increase PTK expression and activity (4,5).…”
mentioning
confidence: 99%
“…Factors such as dietary K intake play a key role in regulating channel activity in the CCD (11,32): high K intake increases, whereas low K intake decreases, SK channel activity in the CCD. We have previously demonstrated that low K intake stimulates the expression of Src family protein tyrosine kinase (PTK) and that inhibition of PTK increases SK channel activity (33,34). However, detailed mechanisms by which PTK-dependent signal transduction pathways regulate ROMK channel activity are still not completely understood.…”
mentioning
confidence: 99%